A Study on Similarity of Websites of Management Institutes Using Data Mining Tools - Saikia, Hemanta; Bhattacharjee, Dibyojyoti (Prabandhan: Indian Journal of Management, 2010)
The World Wide Web has played an important role in presenting the data, even from geographically distant locations, easily accessible to users all over the world. A website is a collection of web pages, consisting of text and images that provide information about a particular topic or organization, twenty four hours a day and seven days a week (Bhattacharjee and Gupta, 2008). Today, it’s a big challenge for management institutes to stay upgraded in the global educational environment. Most of the management institutes provide information about students, courses, faculty, staff and facilities available and other details through their websites and accordingly market themselves. All this information is useful for the students, guardians, scholars as they get a bird’s eye view about the institute. Having a website helps the administration of any institute to provide information about their services- namely admission, results, rules, placement, etc. and accordingly, diminishes the work load of the employees to a great extent.